2014
DOI: 10.1097/scs.0000000000000483
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies and Psychological Distress Among Mothers of Patients With Nonsyndromic Cleft Lip and Palate and the Family Impact of This Disorder

Abstract: The current study aimed to investigate the coping strategies and level of psychological distress in mothers of patients with cleft lip and palate (CLP) and the family impact of this disorder. Participants were mothers of 55 children or adolescents with nonsyndromic CLP recruited from families attending a CLP clinic and 2 university hospitals in Mashhad, northeast of Iran. Family impact, psychological distress, and coping strategies were assessed using validated psychological questionnaires including Family Imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…This finding agrees in part with observations of Kramer et al 25 , who reported that coping problems among families of children with cleft lip (whether unilateral or bilateral) increased compared to families with children having CLP or isolated cleft palate. This finding could be explained based on the more severe impact of bilateral cleft lip and cleft lip/palate on the facial appearance of the child or to avoidant rather than problemsolving coping strategies in the parents 35 . Social support has been highlighted as being useful in the process of coping, as well as perceived support from professionals involved in the child's care 35 39 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding agrees in part with observations of Kramer et al 25 , who reported that coping problems among families of children with cleft lip (whether unilateral or bilateral) increased compared to families with children having CLP or isolated cleft palate. This finding could be explained based on the more severe impact of bilateral cleft lip and cleft lip/palate on the facial appearance of the child or to avoidant rather than problemsolving coping strategies in the parents 35 . Social support has been highlighted as being useful in the process of coping, as well as perceived support from professionals involved in the child's care 35 39 .…”
Section: Discussionmentioning
confidence: 99%
“…This finding could be explained based on the more severe impact of bilateral cleft lip and cleft lip/palate on the facial appearance of the child or to avoidant rather than problemsolving coping strategies in the parents 35 . Social support has been highlighted as being useful in the process of coping, as well as perceived support from professionals involved in the child's care 35 39 . Support from friends and family has been linked to lower distress, better adjustment, and less negative family impact, possibly due to social support providing greater feelings of belonging, self-esteem, a positive outlook, and a greater sense of value 39 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Hasanzadeh et al, in their study demonstrated that the mothers of children with cleft lip and palate faced chronic psychological disorders more frequently. 13 …”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] Hasanzadeh's study demonstrated that the mothers of children with cleft lip and palate are faced with chronic psychological disorders more often. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%